DEVELOPMENT OF ELECTRONIC ARCHIVES MANAGEMENT LEARNING MEDIA (E-ARCHIVING) USING THE MICROSOFT ACCESS APPLICATION FOR STUDENTS OF SMKN 40 JAKARTA - Putri Aisyah Salsabil; Marsofiyati; Nadya Fadillah F (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to develop an Electronic Archives Management (E-Archive) learning media using Microsoft Access for students at SMKN 40 Jakarta. The method used is Research and Development with a 4D development model (Define, Design, Develop, and Disseminate), although this study was limited to the first three stages due to time constraints. The product developed is a digital learning module integrated with Microsoft Access, designed to enhance students' understanding of archiving practices in the digital era. Validation results from material, design, and media experts yielded an average score of 91%, categorized as "very feasible," while practicality tests involving 36 students through individual, small group, and large group trials produced an average score of 92%, categorized as "very practical." These findings indicate that the media is both feasible and practical for use in teaching archival management. The research contributes by offering updated instructional content, an interactive design suited to current student preferences, and a user guide to facilitate learning with Microsoft Access. Future studies are encouraged to expand testing, integrate broader topics, and explore alternative platforms beyond Microsoft Access to improve accessibility and adaptability.